2018
DOI: 10.1159/000495137
|View full text |Cite
|
Sign up to set email alerts
|

The HPV16 E1 Carboxyl Domain Provides a Helper Function for Adeno-Associated Virus Replication

Abstract: Background/Aims: Recombinant adeno-associated virus (rAAV) is now in the clinic, yet production of rAAV remains problematic. We previously determined that human papillomavirus type 16 (HPV16) E1 protein boosts rAAV yields and E1 enhances AAV Rep78’s replication-related biochemistries. Here, we deletion-mapped the helper domain within E1 to help glean its mechanism of action. Methods: Rep78-E1 interaction was analyzed by Gal4-based yeast two-hybrid (Y2H)-cDNA assay. rAAV DNA replication was studied by AAV/helpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The role of papillomaviruses, especially HPV-16, in AAV biology gained great interest in the past years after it was found that both HPV-16 and AAV can infect and reside in cervical cancer tissue and that AAV reduces the risk of developing HPV-16-induced cervical cancer [ 10 , 215 , 216 , 217 , 218 ]. A number of studies have addressed the molecular interaction between HPV-16 and AAV in coinfected cells, resulting in the identification of HPV-16 helper functions for AAV replication [ 219 , 220 , 221 , 222 , 223 ]. However, it turned out that HPV-16 may not be a complete helper virus for AAV, as AAV does not replicate very efficiently when solely HPV-16 helper factors are present.…”
Section: Helper Viruses and Aavmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of papillomaviruses, especially HPV-16, in AAV biology gained great interest in the past years after it was found that both HPV-16 and AAV can infect and reside in cervical cancer tissue and that AAV reduces the risk of developing HPV-16-induced cervical cancer [ 10 , 215 , 216 , 217 , 218 ]. A number of studies have addressed the molecular interaction between HPV-16 and AAV in coinfected cells, resulting in the identification of HPV-16 helper functions for AAV replication [ 219 , 220 , 221 , 222 , 223 ]. However, it turned out that HPV-16 may not be a complete helper virus for AAV, as AAV does not replicate very efficiently when solely HPV-16 helper factors are present.…”
Section: Helper Viruses and Aavmentioning
confidence: 99%
“…Similarly, You et al found that the same set of HPV-16 proteins can enhance AAV replication in epithelial raft cultures [ 222 ]. The HPV-16 helper factor E1 has recently been investigated in more detail, and it has been found that its helper effect can be attributed specifically to the E1 carboxyl domain [ 221 ]. In vivo and in vitro experiments have revealed that the AAV Rep and the HPV-16 E1 proteins can directly interact and modulate the Rep ATPase activity [ 224 , 225 ].…”
Section: Helper Viruses and Aavmentioning
confidence: 99%